Tomb and Temple : Reimagining the Sacred Buildings of Jerusalem. - Griffith-Jones, Robin (Boydell Studies in Medieval Art and Architecture Ser., 2018)
Essays exploring the influence of the sacred buildings of Jerusalem on architecture worldwide.